Application of the velocity-less prestack time migration to the 2D marine line - Tertyshnikov, Konstantin; Bóna, Andrej; Pevzner, Roman; Urosevic, Milovan (SEG, 2012)
Information about seismic velocities is an important and integral part of the seismic imaging process. The task of defining the velocity model is usually quite difficult, especially in regions with a complex geological structure and in new prospecting areas. One emerging way of obtaining a velocity model is to apply a “velocity-less” prestack time migration to the data. Here we describe an application of the velocity-less prestack time migration technique to the real a dataset of a marine 2D seismic line from the North West shelf of Australia and show a comparison of the results with Kirchhoff prestack time migration. The presented algorithm is based on an estimation of local event slopes (horizontal slownesses) in common-shot and common-receiver gathers. These attributes allow us to derive the complete information to be able to construct a time migrated image. The output of the algorithm is three parameters: migration velocity, vertical traveltime and horizontal position of the migrated reflection point. Herein we use the obtained migration velocities as an input velocity model for the Kirchhoff time migration. This experiment on the real dataset demonstrates the promising practical effectiveness of the presented velocity-less prestack time migration algorithm.